Aberrant Methylation of Ribonucleotide Reductase Subunit M2 Is Closely Associated with Oral Cancer - Kho, Goot Heah; Froemming, Gabriele Ruth Anisah; Zain, Rosnah B; Thong, Kwai Lin (IDOSI Publications, 2016)
Gene inactivation by promoter hypermethylation is a common occurrence in the development of various human cancers including oral cancer. Previous evidences observed that DNA methylation play a vital role in the carcinogenesis of oral cancer. The aim of this study was to analyze methylation status and protein expression of RRM2 in oral cancer. Archival tissues of oral cancer and healthy mucosa tissues were retrieved for the study. The methylation status of RRM2 was examined by methylation specific polymerase chain reaction and its protein expression was measured by immunohistochemistry. In the present study, frequency of aberrant methylation of RRM2 was 80% (n=32) in tumour tissues, whereas such methylation status was negatively detected in normal mucosa. In addition, 20 % (n=8) for RRM2 immunoreactivity was revealed in tumour tissues. In tumour tissues, RRM2 promoter hypermethylation was frequently associated with its reduced protein expression. Thus, epigenetic inactivation of RRM2 through promoter hypermethylation may be important in the oral cancer progression and assessment of RRM2 methylation status in oral cancer may become a potential biomarker for early detection in oral cancer.